Tradisi Lisan di Sambas: Cerita Rakyat dan Nasihat Adat dalam Pembentukan Identitas Melayu - Sunandar; Tomi; Lamazi; Sri Sunantri; Iqbal (CV Global Research Publication, 2026)
Oral tradition constitutes one of the most important elements in transmitting cultural values and shaping collective identity. Among the Sambas Malays of West Kalimantan, oral tradition encompasses folktales, proverbs, pantun, customary advice, and historical narratives that preserve collective memory while transmitting Islamic and cultural values across generations. This study examines the role of oral tradition in constructing Sambas Malay identity through the perspectives of cultural memory, cultural identity, and the interaction between adat and Islam. Employing a qualitative descriptive approach, data were collected through field observations, interviews with community leaders and traditional authorities, and documentary studies. The analysis draws upon Jan Vansina’s theory of oral tradition, Stuart Hall’s concept of cultural identity, Jan Assmann’s cultural memory, and Clifford Geertz’s interpretation of religion as a cultural system. The findings demonstrate that oral tradition functions not merely as folklore but as a cultural institution that constructs collective identity, preserves historical consciousness, and integrates customary norms with Islamic values. Consequently, oral tradition serves as a strategic medium through which Sambas Malay society maintains its cultural continuity amid contemporary social transformation.